PENILAIAN USAHA BADAN LAYANAN UMUM DAERAH TRANSJAKARTA BUSWAY TAHUN 2010 - , Muliani Sulya Fajarianti, SE, Dr. Wakhid Slamet Ciptono, M.B.A., M.P.M. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In the application/context of land transport in particular synergy Bulk Transport (Mass Rapid Transport / MRT) in an urban environment, a requirement that a transport ministry agency of good land and managed properly. During the period of 5 (five) last year, local transportation, especially in urban areas experienced the process of becoming a public service agencies, non-profit, not privatization, or the companies that make money the General Services Board Institute Regional (BLUD). This is the institutions of government units to know the concept of Quasi-Public Goods, where funding could be sourced from APBD and income from APBN, besides that BLUD agency has the authority to obtain revenue from paid services community as a a functional acceptance. In Indonesia, especially the province of DKI Jakarta as the capital of the Republic of Indonesia, which has a concept referred to MRT, will apply in accordance with the objectives of local government and facilitate the means of public transport infrastructure also can be managed with special management in order to provide optimal service, economical, and efficient for the users of such transportation. This is because the future of public service aspect to the specialized management pattern is not referred to by the institutions should be purely local government bureaucracy, but held by the managed device ala the business (business like). As a service organization that is non-profit, a BLUD can not escape the economic calculations in applying the tariff calculated on the basis of service with unit cost. The understanding of the subsidies for BLUD in this case is the cost that must be issued by the State due to disparities / differences in market prices with prices for certain services determined by local governments in an effort to meet the needs of the community generally. For that, through this research the main objective as an alternative application of BLUD institutional management systems such as PT. Kereta Api Indonesia (KAI). Should be evaluated and conducted a comprehensive assessment in order to meet the technical requirements of substantive and operational and administrative requirements with the assessment criteria in accordance with existing regulations, the right way and analysis. Research conducted in-TransJakarta Busway BLUD Provincial Government xvi of DKI Jakarta by using secondary data and the use of qualitative, descriptive research case studies that explain, summarize the various conditions, different circumstances or different variables which arise in society which became the subject of research on what is occurred. The data consist of financial statements and data profiles Regional Public Service Agency, and other supporting data. Initial stage is to project the estimated value of BLUD financial statements based on expectations TransJakarta Busway operating income growth rates. The results of this projection is used to estimate free future cash flows generated by these BLUD. Estimation is then performed and the discount rate used to discount a tariff setting and obtain the present value of those cash flows. Next use the income approach and do the testing method or the Discounted Cash Flow Asset Based Test Approach method to analyze the feasibility category weighting values in accordance with business standards today. However, researchers in preparing this study also had many weaknesses or limitations of the study of this research. It is expected that this research can be used as reference for subsequent studies. Based on this research, produced estimates of the value of these enterprises in general, complete and comprehensive associated with the resulting performance of operating income and other income of the average fluctuations can reach 115,98% and total valuation of Administration document BLUD is 84,9. The Income approach method found that BLUD Transjakarta values range from Rp141.358.000.000,- , Rp111.785.000.000,- and Rp73.370.000.000,- while relative valuation result in Rp108.837.666.667,- and Asset valuation approach gave the value of Rp98.755.403.085,- with the mean value of the two methods of Rp104.804.761.234,-. The value generated from these estimates reflect a few things that can affect whether or not a feasible or public service agency of this area should be retained as a full BLUD, the increased status, or to be reviewed. However, in order to improve the quality assessment of BLUD, should have conducted a review of assessment methods and analysis for BLUD that have implemented financial management BLUD pattern during 5 (five) years based on the regulations established by each Regional Head and at least have accordance with the standards required assessment criteria.